Cocrystal of Ibuprofen-Nicotinamide: Solid-State Characterization and In Vivo Analgesic Activity Evaluation - Yori Yuliandra; Erizal Zaini; Syofyan Syofyan; Wenny Pratiwi; Lidiya Novita Putri; Yuti Sahra Pratiwi; Helmi Arifin (MDPI AG, 2018)
Ibuprofen is classified as a BCS class II drug which has low solubility and high permeability. We conducted the formation of the cocrystalline phase of ibuprofen with coformer nicotinamide to increase its solubility. The purpose of this study was to characterize the solid state of cocrystalline phase of ibuprofen-nicotinamide, determine the solubility, and evaluate its in vivo analgesic activity. The cocrystal of ibuprofen-nicotinamide was prepared by a slow evaporation method. The solid-state characterization was conducted by powder X-ray diffraction (PXRD) analysis, differential thermal analysis (DTA), and scanning electron microscopy (SEM). To investigate the in vivo analgesic activity, 28 male Swiss-Webster mice were injected with acetic acid 0.5% following oral administration of intact ibuprofen, physical mixture, and its cocrystalline phase with nicotinamide (equivalent to 26 mg/kg ibuprofen). The number of writhes was counted, and pain inhibition was calculated. All data were analyzed with one-way ANOVA followed by Duncan’s Multiple Range Test (95% confidence interval). The results revealed that a new cocrystalline phase was successfully formed. The solubility testing showed that the cocrystal formation enhanced the solubility significantly as compared with the physical mixture and intact ibuprofen. A significant increase in the analgesic activity of cocrystal ibuprofen-nicotinamide was also confirmed.